Daily cleaning activity and diversity of clients of the barber goby, Elacatinus figaro, on rocky reefs in southeastern Brazil - Sazima, I; Sazima, C.; Francini, R. B.; Moura, R. L. (Kluwer Academic Publ, 2000)
Gobies of the genus Elacatinus are regarded as the most specialised cleaner fishes in the western tropical Atlantic, yet there are no studies on these cleaners in the southern portion of West Atlantic. We studied the diversity of clients and the daily cleaning activity of the barber goby, Elacatinus figaro, on rocky reefs in southeastern Brazil (23-24 degrees S). A total of 34 fish client species in 16 families were recorded over 484 cleaning events. The most frequent clients were damselfishes, Pomacentridae (37.9% of cleaning events) and grunts, Haemulidae (16.9%). Planktivores were the most frequently attended trophic category, and two species in that category accounted for about a half (44%) of the total cleaning events. Size of clients ranged 4.5-55 cm and most individuals were medium-sized (12-30 cm); as the barber goby ranged 2-4.5 cm, clients were 1.5 to 15 times larger than the cleaner was. Cleaning activity started at dawn and ended shortly before nightfall, the highest frequency of interactions occurring at early morning (nocturnal clients) and mid-afternoon (diurnal clients). By midday the frequency of cleaning events decreased and their duration increased. A total of 109 +/- 3 cleaning events and 30 +/- 1 min of cleaning activity were estimated per cleaning station per day, both figures low when compared to those recorded for cleaner fishes in tropical areas of the western Atlantic and Indo-Pacific.
Keywords: Gobiidae; cleaning symbiosis; cleaning stations; fish clients; feeding habits; planktivores; western South Atlantic